Recurrent dermatofibrosarcoma protuberans treated with Mohs micrographic surgry - Kodric, M... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
We present the case of a 68-year-old woman with a recurrent dermatofibrosarcoma protuberans on the neck and the upper back, surgically treated four times over a yearlong period. Neither radiotherapy nor chemotherapy have been effective. After the last recurrence the Mohs micrographic surgery has been applied. The tumor has been excised and cut in aconsiderable number of fragments, which have then been examined microscopically. A second procedure has been necessary to completely remove the tumoral mass. Four months later there have been no signs of local recurrence any more. The Mohs micrographic surgery is the treatment of choice for dermatofibrosarcoma protuberans, since classical surgical excision would have been, as our case reveals, difficult and vain.
Keywords: Aged; Dermatofibrosarcoma; dermatologija; kirurško zdravljenje; Mohs surgery; Neoplasm recurrence, local; rak (medicina); sarkom; Surgery; Therapy; Treatment outcome; zdravljenje